Pengembangan cetak kemasan melalui keterampilan cetak sablon dan vacuum forming - Dian Cahyadi; Lanta L. (DEDIKASI, 2019)
The partner of this Community Partnership Program (PKM) was a student and teacher of YYPP SMK Wonomulyo Distric of Polewali Mandar of Sulawesi Barat Province. The problems were: (1) lack of knowledge about screen printing and heat molding wrapper so it has an attractive appearance, (2) easy to print screen printing and heat-forming packaging, (3) packaging products IRT / SME, and (4) the quality of the packaging print production sellable. External target is the SME / Industry Households have an interesting product packaging. The methods used are: lectures, demonstrations, discussions, question and answer, and counterparts. The results obtained are: (1) The partners have the skills to print T-shirts, (2) partners have the skills to print T-shirts, (3) the partner has the ability to produce attractive packaging